2017
DOI: 10.1007/s00442-017-3960-y
|View full text |Cite
|
Sign up to set email alerts
|

Similar alpha and beta diversity changes in tropical ant communities, comparing savannas and rainforests in Brazil and Indonesia

Abstract: Local biodiversity can be expected to be similar worldwide if environmental conditions are similar. Here, we hypothesize that tropical ant communities with different types of regional species pools but at similar habitat types in Brazil and Indonesia show similar diversity patterns at multiple spatial scales, when comparing (1) the relative contribution of alpha and beta diversity to gamma diversity; (2) the number of distinct communities (community differentiation); and (3) the drivers of β-diversity (species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…As a result, total β‐diversity was highest in primary forest and lowest in Eucalyptus forest (Figure S2.12). This was largely driven by species turnover, with nestedness forming only a small component in line with most studies (Soininen, Heino, & Jianjun, ) and particularly ants (Luis, Silva, Souza, Solar, & Neves, ; Schmidt et al., ). In disturbed habitats turnover decreased, probably due to a larger proportion of generalist species that tolerate a broader range of conditions, reducing the effects of environmental filtering.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As a result, total β‐diversity was highest in primary forest and lowest in Eucalyptus forest (Figure S2.12). This was largely driven by species turnover, with nestedness forming only a small component in line with most studies (Soininen, Heino, & Jianjun, ) and particularly ants (Luis, Silva, Souza, Solar, & Neves, ; Schmidt et al., ). In disturbed habitats turnover decreased, probably due to a larger proportion of generalist species that tolerate a broader range of conditions, reducing the effects of environmental filtering.…”
Section: Discussionsupporting
confidence: 81%
“…As a result, total b-diversity was highest in primary forest and lowest in Eucalyptus forest ( Figure S2.12). This was largely driven by species turnover, with nestedness forming only a small component in line with most studies (Soininen, Heino, & Jianjun, 2018) and particularly ants (Luis, Silva, Souza, Solar, & Neves, 2017;Schmidt et al, 2017…”
Section: Differences In B-diversity Between Habitatssupporting
confidence: 73%
“…Partition of taxonomic beta diversity revealed that most of the variation in ant community composition was due to species replacement, as balanced changes in species abundance meant a relatively stable regional pool of species with varying number of individuals at each site, leading to species turnover between fragments. Other studies have also found larger contributions of species replacement in comparison with species loss at local and landscape scales (Schmidt et al 2017), while the species loss/gain component seems to be more important at regional or even larger scales (Schmidt et al 2017) or in regions where strong For each matrix, the proportion of inertia explained by constrained, conditional (year) and unconstrained components is showed c Independent variables included in the formula of the best models are shown, with their P-value indicated in superscripts (*p \ 0.05; **p \ 0.01) environmental or historic gradients occur (Baselga 2010). In our Chaco Serrano forest, taxonomic and functional composition were poorly affected by edge/ interior position, indicating that the higher diversity consistently found at the edges was not strongly linked to a compositional pattern.…”
Section: Effects On Community Composition and Mechanisms Involvedmentioning
confidence: 88%
“…This beta diversity can be divided into components that are in turn linked to the mechanisms underlying community differences, by indicating either replacement of species between sites or species loss (Gaston and Blackburn 2000). The response of beta diversity components to environmental factors (Soininen et al 2018) has been recently explored for ant communities (Bishop et al 2015;Schmidt et al 2017). However, to our knowledge, no study has yet simultaneously evaluated the influence of habitat loss and edge effects on taxonomic and functional diversity of ant communities, while incorporating beta diversity components in order to disentangle such effects.…”
Section: Introductionmentioning
confidence: 99%
“…The relative contribution of these two components has been shown to be useful for understanding what causes beta diversity patterns at large scales (Dobrovolski et al, 2012;Leprieur et al, 2011;Svenning et al, 2011). So far, turnover has been frequently found to be the most important driver of beta diversity in both aquatic and terrestrial ecosystems at large scales (Schmidt et al, 2017;Viana et al, 2016). However, processes responsible for shaping species replacement are still poorly explored (Baselga, 2010;Schmidt et al, 2017;Soininen, Heino, & Wang, 2018).…”
mentioning
confidence: 99%